2014
DOI: 10.1007/s11764-014-0347-5
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors among breast, prostate, and colorectal cancer survivors: a US population-based case-control study, with comparisons by cancer type and gender

Abstract: Purpose The aim of this study is to compare health behaviors between breast, prostate, female, and male colorectal cancer survivors to noncancer controls, stratified by short- and long-term survivors, and between cancer types and genders. Methods A 3:1 population-based sample of breast (6,259), prostate (3,609), female colorectal (1,082), and male colorectal (816) cancer survivors from the 2009 Behavioral Risk Factor Surveillance System survey were matched to noncancer controls on age, gender, race/ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
96
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 33 publications
11
96
1
2
Order By: Relevance
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 90%
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Female survivors further from diagnosis were more likely to smoke, whereas male survivors may be less physically active over time. Meaning that, similar to cancer survivors in general, health behavior support is needed in the long-term for all AYA survivors [31]. Cervical cancer was the most common female cancer diagnosis in our population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that most cancer patients do not adhere to the PA guidelines of the American Cancer Society, and many are less active than their age-matched, non-cancer peers [10]. In light of research demonstrating the benefits of PA for cancer patients, it is clear that health professionals have a duty of care to more regularly discuss PA during their consultations.…”
Section: Discussing Physical Activity With Cancer Patientsmentioning
confidence: 99%